In vivo and in vitro protein digestibility in juvenile bagrid catfish Mystus nemurus (Cuvier and Valenciennes 1840) fed soybean meal-based diets - Roshada Hashim; Sharifah Rahmah; Mohammed Aliyu-Paiko (John Wiley & Sons Ltd, 2024)
Aquaculture ResearchVolume 47, Issue 5 p. 1392-1401 First published: 01 October 2014